A novel MPPC-based detection method for wide range X/γ radiation dose rate measurement. (1st July 2022) - Zhang, Y.; Li, D.; Tong, T.; Huang, X.; Wang, Y.; Liu, Y.; Zhu, M.; Zhou, W.; Zhang, W.; Zhang, Z.; Shi, R.; Wei, L.
Abstract: With the increasing application of nuclear technology in many fields, in order to meet the requirements for the measurement range of nuclear radiation dose rate in different fields, a new X/ γ dose rate measurement method is proposed in this paper. Using MPPC to couple CsI(TI) scintillator, combined with continuous periodic charges integration electronics, a detector system was developed. It enables MPPC to work in two different regions, avalanche and proportional, and realizes a wide range of dose rate measurement through gain changes between different regions. In experiments, this method measured the γ radiation dose rate in radiation fields between 0.1 μGy/h to 400 Gy/h 60 Co. Additionally, it measured an energy resolution for 137 Cs at 9.4% at a dose rate of 1 mGy/h. These results demonstrate that this method is both accurate and feasible.